Some pharmacokinetic parameters of salvianolic acid A following single-dose oral administration to rats - Jialin Sun; Junke Song; Wen Zhang; Fanbo Jing; Wen Xu; Ping Leng; Xianghua Quan; Guanhua Du; Zhongguo Sui (Taylor & Francis Group, 2018)
Context: Salvianolic acid A (Sal A) is a hydrophilic bioactive compound isolated from Salvia miltiorrhiza Bunge (Lamiaceae). It exerts beneficial effects after oral administration on diabetic complications. Objective: To systematically study the absorption, distribution and excretion of Sal A after single-dose oral administration. Materials and methods: Animal experiments were conducted in Sprague-Dawley rats. Plasma was sampled at designated times after oral doses of 5, 10 and 20 mg/kg, and an intravenous dose of 50 μg/kg. Tissues were harvested at 10, 60 and 120 min postdosing. Bile, urine and feces were collected at specified intervals before and after dosing. Absorption and distribution characteristics were analyzed by LC-MS, and excretion characteristics were analyzed by UPLC-MS/MS. The Caco-2 cell model was applied to investigate potential mechanisms. Results: The Cmax (5 mg/kg: 31.53 μg/L; 10 mg/kg: 57.39 μg/L; 20 mg/kg: 111.91 μg/L) of Sal A increased linearly with doses (r> 0.99). The calculated absolute bioavailability was 0.39-0.52%. Transport experiment showed poor permeability and the ratio of PB-A to PA-B was 3.13-3.97. The highest concentration of Sal A was achieved in stomach followed by small intestine and liver, and it could also be detected in brain homogenate. Approximately 0.775% of its administered dose was excreted via feces, followed by bile (0.00373%) and urine (0.00252%). Discussion and conclusions: These results support the future development of Sal A as an oral drug for the treatment of diabetic complications. Future research should be conducted to investigate the reason for its poor bioavailability and improve this situation.